The role of the category of knowledge in the Plato’s philosophy - Briukhovetskyi, Mykola (Actual Problems of Mind, 2017)
The paper attempts in elucidating the knowledge understanding in various subdisciplines of the philosophical system by Plato, in particular, in his epistemology, ontology, political philosophy and ethics. The author concludes that the category of knowledge as knowledge of the essence takes a central place in the main subdisciplines of Plato’s philosophy.